2004
DOI: 10.1111/j.1365-2362.2004.01319.x
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of total homocysteine plasma concentration in type 2 diabetes

Abstract: Age, creatinine, folate, vitamin B12, and to a minor extent, sex, smoking, TT genotype and systolic BP were significantly associated with Hcy plasma concentration in type 2 diabetes, whereas no significant associations were noted with diabetes-related variables.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
9
0
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 53 publications
3
9
0
2
Order By: Relevance
“…The elevated level of serum homocysteine in females >50 years old was found to be associated with high levels of serum lipids mainly LDL and triglycerides and low level of HDL (data is not shown), this may shed light on the role of estrogen on the metabolism of homocysteine at menopause and how this could form a risk factor of CHD in females at this age. In this study we are consistent with those of Russo et al (2004) and colleagues (WHO-ISH, 1999), who found age and sex were significantly associated with homocysteine level in type 2 diabetes. There is clear evidence that homocysteine levels can be lowered by administration of supplemental folate, with or without pyridoxine.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The elevated level of serum homocysteine in females >50 years old was found to be associated with high levels of serum lipids mainly LDL and triglycerides and low level of HDL (data is not shown), this may shed light on the role of estrogen on the metabolism of homocysteine at menopause and how this could form a risk factor of CHD in females at this age. In this study we are consistent with those of Russo et al (2004) and colleagues (WHO-ISH, 1999), who found age and sex were significantly associated with homocysteine level in type 2 diabetes. There is clear evidence that homocysteine levels can be lowered by administration of supplemental folate, with or without pyridoxine.…”
Section: Discussionsupporting
confidence: 82%
“…Predominant among the causes of mortality and major morbidity is thromboembolism, followed by cerebrovascular accident, peripheral arterial thrombosis and myocardial infarction. Hyperhmocysteinemia, regardless of its cause, is an independent risk factor for stroke, coronary or peripheral artery disease (Russo et al, 2004). The objective of this study is to examine if there is an association between elevated plasma level of homocysteine with age and sex in diabetic and nondiabetic coronary heart disease patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It may be caused by increased production, decreased removal, or both. Although homocysteine concentration is inversely related to renal function (7,15) and is associated with the development of microalbuminuria (16), the precise kinetic mechanism(s) leading to the hyperhomocysteinemia of diabetes with nephropathy has never been investigated. Also, a possible link(s) between insulin resistance and alterations of homocysteine metabolism is largely unknown (12,17).…”
mentioning
confidence: 99%
“…Russo ve ark. [26] , 312 DM'li olgu-da homosistein ile HbA1c ve AKŞ arasında ilişki saptamamış olmamalarına karşın; Abdella ve ark. [20] , 358 tip 2 diyabetli hastada yaptıkları çalışmada homosistein ve HbA1c arasında ilişki saptamışlardır.…”
Section: Hdlkolesterolunclassified